The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1038/nchembio.1387
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the hidden functional diversity of an enzyme family

Abstract: Millions of protein database entries are not assigned reliable functions, preventing the full understanding of chemical diversity in living organisms. Here, we describe an integrated strategy for the discovery of various enzymatic activities catalyzed within protein families of unknown or little known function. This approach relies on the definition of a generic reaction conserved within the family, high-throughput enzymatic screening on representatives, structural and modeling investigations and analysis of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
129
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(132 citation statements)
references
References 39 publications
0
129
0
Order By: Relevance
“…Although these methods outperform historical methods, continued improvement is necessary to ensure accurate annotation of function (2). A greater swath of functional space can be covered by screening substrates in a high-throughput manner on multiple enzymes from a family (3,4). Family-wide substrate profiling offers a data-rich resource.…”
mentioning
confidence: 99%
“…Although these methods outperform historical methods, continued improvement is necessary to ensure accurate annotation of function (2). A greater swath of functional space can be covered by screening substrates in a high-throughput manner on multiple enzymes from a family (3,4). Family-wide substrate profiling offers a data-rich resource.…”
mentioning
confidence: 99%
“…Orthogonal to the genome-wide study discussed above, Bastard et al (30) demonstrated the use of an integrated strategy for exploring the functional diversity of a previously undescribed enzyme family, DUF849 (see Fig. 1 for general reaction and representative substrates).…”
Section: Screening To Assess Substrate Ambiguitymentioning
confidence: 99%
“…Many of the widespread DUFs in bacteria are biologically essential, and the importance of prioritizing these DUFs has been recognized in recent years (10). Before this study, only one DUF family, the DUF849 family of 922 proteins, had been evaluated in large scale by a single report (11), which heavily relied on previously published enzymatic activity and catalytic mechanism/ liganded structure of one of its members (35,36). Recognizing the difficulties associated with DUF functional assignment, we attempt to apply an integrated "genomic enzymology" strategy that had only been used for functional characterization of members of families with known functions (37,38).…”
Section: Synergistic Analysis Of Ssns and Gnns Enables The Predictionmentioning
confidence: 99%
“…However, the assignment of functions to uncharacterized proteins is challenging (11)(12)(13). The methods now available for discovering the functions of uncharacterized proteins, including DUFs, are inefficient and often depend on inference from the functions of characterized homologs (11). Therefore, new strategies are required to confront and solve the functional assignment challenge.…”
mentioning
confidence: 99%
See 1 more Smart Citation